THE EFFECT OF PRODUCT QUALITY, PRODUCT DESIGN, AND PROMOTION ON THE PURCHASE DECISION OF NIRO GRANITE IN UD BANGUN JAYA PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to analyze the effect of product quality, product design, and promotion on the purchasing decision of Niro brand granite at UD Bangun Jaya Pekanbaru both partially and simultaneously. The population in this study is not known with certainty, so the sample was determined using the probability Sampling method, namely convenience Sampling, and the number of pieces in this study using the Roscow formula, which resulted in a total sample of 100 people consisting of all customers at UD Bangun Jaya Pekanbaru. The research method uses multiple Linear Regression Equation analyses using the SPSS Version 21 application. The results of the overall study of product quality, product design, and promotion variables affect the purchasing decision of Niro brand granite at UD Bangun Jaya Pekanbaru. Variables of product quality, product design, and advertising have contributed 74.8% to the purchasing decision variables for the N iro Granite at UD Bangun Jaya Pekanbaru. However, there is still a 25.2% influence on other factors not included in the study.